Bioceramic Bone Graft Substitute for Treatment of Unicameral Bone Cysts. (August 2016) - Fillingham, Yale A; Cvetanovich, Gregory L; Haughom, Bryan D; Erickson, Brandon J; Gitelis, Steven
Purpose: To review the outcome of 12 patients who underwent debridement and injection of bioceramic for unicameral bone cyst (UBC). The resorption rate of the bioceramic was estimated by both traditional and novel methods. Methods: Records of 10 males and 2 females aged 6 to 34 years who underwent debridement and injection of bioceramic for UBC and were followed up for a mean of 41 (range, 26–57) months were reviewed. Functional outcome was assessed using the self-completed Musculoskeletal Tumor Society (MSTS) questionnaire. Radiological outcome was assessed using both original and modified Neer Outcome Rating System. The resorption rate of the bioceramic was estimated using both traditional and novel (ImageJ) methods. Results: The mean MSTS score was 29.7 (range, 28–30) indicating excellent functional outcome. Of the 12 patients, 9 achieved complete healing and 3 had a residual cyst of 1%, 11%, and 52%. The last was considered a local recurrence, and the patient underwent repeat percutaneous injection of the bioceramic 1.5 years later and remained disease-free 4 years later. The mean resorption rate was 29% faster when estimated using the traditional rather than the ImageJ method (0.47 vs. 0.33 cm 3 /day, p=0.02). In the patient with recurrence, the resorption rate was faster than the average (0.68 vs. 0.33 cm 3 /day). Conclusion: A single percutaneous injection of the bioceramic for UBC achieved good functional and radiological outcome while avoiding donor-site morbidity.